Head-to-Head Comparison of Tissue Factor-Dependent Procoagulant Potential of Small and Large Extracellular Vesicles in Healthy Subjects and in Patients with SARS-CoV-2 Infection - Marta Brambilla; Roberto Frigerio; Alessia Becchetti; Alessandro Gori; Marina Cretich; Maria Conti; Antonella Mazza; Martino Pengo; Marina Camera (Biology, 2023)
The relative contribution of small (sEVs) and large extracellular vesicles (lEVs) to the total plasma procoagulant potential is not yet well defined. Thus, we compared total and TFpos-sEVs and -lEVs isolated from healthy subjects and COVID-19 patients during the acute phase of the infection and after symptom remission in terms of (1) vesicle enumeration using nanoparticle tracking assay, imaging flow cytometry, and TF immunofluorescence localization in a single-vesicle analysis using microarrays; (2) cellular origin; and (3) TF-dependent Xa generation capacity, as well as assessing the contribution of the TF inhibitor, TFPI. In healthy subjects, the plasma concentration of CD9/CD63/CD81pos sEVs was 30 times greater than that of calceinpos lEVs, and both were mainly released by platelets. Compared to lEVs, the levels of TFpos-sEVs were 2-fold higher. The TF-dependent Xa generation capacity of lEVs was three times greater than that of sEVs, with the latter being hindered by TFPI. Compared to HSs, the amounts of total and TFpos-sEVs and -lEVs were significantly greater in acute COVID-19 patients, which reverted to the physiological values at the 6-month follow-up. Interestingly, the FXa generation of lEVs only significantly increased during acute infection, with that of sEV being similar to that of HSs. Thus, in both healthy subjects and COVID-19 patients, the TF-dependent procoagulant potential is mostly sustained by large vesicles.